Чернігівський Троїцький монастир у 1943–1962 рр. - Юхно, Ф. (Сiверянський лiтопис, 2019)
У статті аналізується становище Чернігівського Троїцького православного монастиря. Розглядається законодавча база та її вплив на діяльність обителі, фінансове
становище та принципи оподаткування. Висвітлюються процеси, які відбувалися
довкола неї – взаємовідносини з органами влади, установами та організаціями, розташованими на його території, питання земельного забезпечення, господарська діяльність та зайнятість монахинь. Звертається увага на заходи, що були спрямовані
на зменшення впливу черниць на прихожан та жителів міста, висвітлюється кампанія
по ліквідації обителі та описуються заходи для дискредитації і закриття монастиря,
показується діяльність архієреїв та ігуменії у відстоюванні монастирських інтересів. The research is caused by the importance of studying various models of coexistence of
government and church, a special place of Orthodox monasteries in people’s life and their
influence on the life of society.
The purpose of this study is to analyze the situation of Chernihiv Trinity Monastery since
the liberation of Chernihiv from the German occupation to its closure, the coverage of events
that took place around the monastery, the characteristics of the relations of nuns with the
authorities.
Exploring the problem, the author used methods of systemicity, objectivity, statistics and
historicism.
The article analyzes the post-war existence of the Chernihiv Trinity Orthodox Monastery,
examines the Soviet religious law and its influence on the activity of the monastery, highlights
the processes that took place around the monastery – the relationship with the authorities,
institutions and organizations located on its territory, land issues and financial situation,
economic activity and employment of nuns.
Separately attention is paid to the measures aimed at reducing the influence of nuns on
parishioners and residents of the city, the campaign on discrediting and liquidation of the monastery
is described, the measures taken by the authorities to close the monastery are described,
the activities of the bishops and abbot interests in the protection of monastery are shown.
As a result, it was established that the position of the Chernihiv Trinity Monastery was
completely dependent on the state religious policy, which was also affected by total taxation,
poor housing, land and financial security, and continuous monitoring of its life.
In the end, the monastery was closed, nuns were evicted and its buildings were transferred
to the use of various organizations and institutions.